1923 Cal. Stat. 695 An Act to Control and Regulate the Possession, Sale and Use of Pistols, Revolvers, and Other Firearms Capable of Being Concealed Upon the Person - (:unkn) unknown (General Publisher, 1923)
Prohibited ownership, possession, or control of any pistol, revolver or concealable firearm by any noncitizen or felony convicts.
--
Keywords: POSSESSION - DANGEROUS PERSONS